Comparative Analysis of Usability and Efficiency of Interface Design Process in Figma and Adobe XD - Muhammad Dyo Haqiqi; Temi Ardiansyah (P3M Politeknik Negeri Bengkalis, 2026)
A variety of platforms are now focused on improving and speeding up the design process by harnessing the growing use of digital technologies in user interface (UI) design. Adobe XD and Figma stand out as two of the most popular tools for user interface and user experience design. User experience can differ due to variations in usability and the effectiveness of the design process, even when both share similar core functions. This study aims to assess the effectiveness and practicality of Adobe XD and Figma. This research utilizes a quantitative descriptive approach, measuring task completion times and leveraging the System Usability Scale (SUS) for evaluation. Twenty students signed up for an informatics program, each bringing with them a solid background in both systems, and successfully completed the survey. Data was gathered using SUS surveys and time observations carried out during the performance of design tasks. According to the data, Figma boasts an impressive average SUS score of 62.75%, while Adobe XD trails behind with a score of 46.75%. Figma outperformed Adobe XD by around 27.98% in executing design tasks. The findings reveal that Figma outshines Adobe XD in terms of efficiency and user-friendliness, especially when it comes to real-time collaboration and a sleek, streamlined interface. These findings aim to guide educational institutions and UI/UX designers in choosing the ideal design platform that aligns with user needs.